Epistemologi Tafsir Maqȃṡidī Wasfī Asyūr Abu Zayd: Analisis Kritis terhadap Buku Nahwa Tafsīr Maqāşidī karya Abu Zayd - Zainuddin Aziz; Romlah Widayati (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2026)
This study aims to identify the book Nahwa Tafsīr Maqāşidī by Waṣfī Asyūr Abu Zayd and formulate the formulation of the methodology structure of his maqāṣidī interpretation while also critiquing it. This study uses library research with a historical, phenomenological, and content analysis approach whose data sources are taken from documentation. The results of the study show that in terms of material and systematics, this book contains a systematic discussion of the methodology of maqāṣidī interpretation that was born from the atmosphere of the scientific climate that is currently renewing the understanding of Islamic texts. The reference sources in this book come from various relevant and credible sources (mu’tabarah) which are very well combined using exploratory and synthetic presentation methods with an epistemological approach. From an ideological perspective, this book is guided by the thoughts of Ahlu Sunnah wal Jama'ah, who prioritize Islamic moderation (wasaṭiyah) for the realization of an Islam that brings mercy to the entire universe (rahmatan li al-'ālamīn). The methodology of maqāṣidī interpretation developed by Abū Zayd in this book only focuses on one dimension of maqāṣidī interpretation, namely the exploration of the Maqāṣid al-Qur'ān. In addition, this method has not fully mapped various aspects related to maqāṣidī interpretation, so that ambiguities are often found in its methodological structure. Therefore, it can be said that this method is still incomplete and not comprehensive. However, some parts are still suitable for application, while others need to be restructured.